KNOWLEDGE, ATTITUDES, AND PRACTICES RELATED TO THE DISPOSAL OF EXPIRED AND UNUSED MEDICATIONS IN HOUSEHOLD IN DUHOK CITY, KURDISTAN REGION, IRAQ - Najmaldin Ezaldin Hassan; Sonia Khalil (Science Journal of University of Zakho)
Unused, unwanted, and expired household medications can accumulate and be improperly disposed of, posing a major national and international public health and environmental concern. This problem is primarily caused by a lack of awareness and understanding of appropriate medicine disposal techniques. This study aimed to assess the knowledge, attitudes, and practices regarding the disposal of unused, unwanted, or expired household medicines among the general public in Duhok city, in the Kurdistan Region of Iraq. Between March 6 and June 6, 2023, 250 participants were interviewed in person using a pre-validated structured questionnaire for this cross-sectional study. The accuracy of the returned questionnaires was verified multiple times. Descriptive statistics were calculated for the sample population's characteristics, and the findings were presented in tables as percentages. Out of the 250 respondents included in the study, 115 (46%) were females, and 165 (66%) were married. A total of 205 (82%) of the respondents had formal education. The most commonly used disposal practice for unused medicines was throwing them in household garbage, as reported by 137 (54.8%). Interestingly, 127 (61.95%) of the participants who disposed of medicines in the garbage had formal education. About 68 (27.2%) of the participants kept unused or unwanted medicines at home for future use or until expiration, followed by giving them to friends and relatives (23, or 18.07%), while a few (12, or 9.27%) burned medicines at home. Significantly, 206 (82.4%) of the respondents did not check the expiry date before taking medicine. A majority of respondents, 155 (62%), held the government responsible for creating awareness about proper medicine disposal. Almost all participants (220, or 88%) felt that improper disposal of unused and expired medicines can affect the environment and health. This study revealed that the most common ways to dispose of unused, unwanted, and expired medication were tossing them in the trash and storing them for later use. There is an urgent need to address the fact that most study participants disposed of medicine in unsafe ways. Nonetheless, the majority of participants agreed that improper disposal of medications poses a threat to public health and the environment. Therefore, both national and local stakeholders urgently need to implement tailored interventions to address the situation.